Oral Health-Related Quality of Life and Satisfaction before and after Treatment with Complete Dentures in Faculty of Dentistry, Tishreen University. (Journal of Hama University, 2020)
Purpose: The aim of this study was to evaluate the impact of treatment with new complete dentures on oral health-related quality of life and satisfaction of edentulous patients attending the Prosthodontic Department in the faculty of dentistry, Tishreen university.Methods: A total of 70 edentulous subjects (37–86 years) treated by undergraduate students at faculty of dentistry, Tishreen university, were accessed. A specific questionnaire for edentulous patients (EDENT) based on the Oral Health Impact Profile (OHIP-EDENT) was applied to collect information on patient oral health-related quality of life. Questions related to the personal satisfaction of the edentulous patients with their complete dentures were also included. The patients were accessed before the treatment, and 3 months after receiving the new dentures. Results: After rehabilitation with new complete dentures, all domains of OHIP-EDENT showed significant improvements. There was also a significant improvement in patient satisfaction after placement of new complete dentures. Furthermore, it was possible to observe association between upper denture satisfaction and age. Conclusion: Conventional complete dentures may have a positive impact on oral health-related quality of life and satisfaction of edentulous patients.